HIV and Sexually Transmitted Infection Incidence and Associated Risk Factors Among High-Risk MSM and Male-to-Female Transgender Women in Lima, Peru. (15th August 2015) - Castillo, Rostislav; Konda, Kelika A.; Leon, Segundo R.; Silva-Santisteban, Alfonso; Salazar, Ximena; Klausner, Jeffrey D.; Coates, Thomas J.; Cáceres, Carlos F.
Abstract : Background: Men who have sex with men (MSM) and male-to-female transgender women (TW) are at increased risk of HIV and sexually transmitted infections (STIs). We evaluated factors associated with incidence of HIV, HSV-2, and chlamydia and gonorrhea (anal and pharyngeal). Methods: We used data from the Comunidades Positivas trial with MSM/TW who have sex with men in Lima, Peru. Participants were asked about sexual risk behaviors and underwent HIV/STI testing at baseline and 9- and 18-month follow-ups. We used discrete time proportional hazards regression to calculate hazard ratios for variables associated with incidence of each STI. Results: Among 718 MSM/TW, HIV incidence was 3.6 cases per 100 person-years. HIV incidence was associated with having an incident STI adjusted hazard ratio (aHR) of 3.73. Unprotected receptive anal intercourse was associated with incident anal chlamydia (aHR 2.20). An increased number of sexual partners increased incident HSV-2 (aHR 3.15 for 6–14 partners and 3.97 for 15–46 partners compared with 0–2 partners). The risk of anal gonorrhea decreased with each sexually active year (aHR 0.94) and increased for unprotected compensated sex (aHR 2.36). The risk of pharyngeal gonorrhea also decreased with each year since sexual debut (aHR 0.95). The risk of anal chlamydia decreased with each sexually active year (aHR 0.96); the risk increased with reports of unprotected sex work (aHR 1.61) and unprotected receptive anal sex (aHR 2.63). All aHRs have P values <0.05. Conclusions: MSM/TW experience high incidence of HIV. Up-to-date prevalence and incidence information and identifying factors associated with infection can help develop a more effective combination prevention response.